Phenotypic changes in Salmonella typhi: observations during the recent upsurge in typhoid cases in Vadodara, Gujarat - Marathe, Anant; Shaikh, Asmabanu; Prajapati, Bhavita (International Journal of Research in Medical Sciences, 2025)
Background: Salmonella enterica serotype typhi is a causative agent of enteric fever (typhoid). The study was aimed at seeing why the S. typhi showing in vitro susceptibility to ceftriaxone required longer treatment for defervescence. We observed phenotypic change characterized by bipolar staining (safety-pin appearance) in the bacilli. We also observed bacilli forming elongated (filamentous forms). We hypothesize a possible association between this structural change in the cell-wall and the resistance pattern of S. typhi. Methods: The study was conducted in a rural hospital with tertiary care facilities. Blood cultures were performed in cases of all the patients with suspected sepsis. The blood cultures were performed on an automated BACT/Alert 3D system. Identification and drug susceptibility of the bacterial isolates are done on VITEK 2. The study comprised 25 blood culture-positive typhoid cases in the last three months. Results: We observed that gram-stained smears made from positive blood culture bottles revealed conspicuous changes in staining pattern of the bacilli. The bacilli showed Bipolar staining (safety pin appearance) of Salmonella enterica serotype typhi under the oil immersion objective. Conclusion: This is the first observational study to investigate the phenotypic change in the staining properties of S. typhi. We hypothesize that this change in staining pattern is associated with structural changes in the bacterial cell wall, which is responsible for S. typhi altered response to antibiotic therapy.